Perlindungan Hukum terhadap Hak Cipta Motor Modifikasi di Indonesia - Anak Agung Bagus Yoga Pramana; I Nyoman Putu Budiartha; Desak Gde Dwi Arini (Warmadewa Press, 2022)
The era of globalization that is happening at this time encourages humans to face technological advances including creativity in modifying motorized vehicles. Motor vehicle modification activities cause changes in the tangible versions of dimensions, engines, and carrying capacity. Changes that occur are closely related to the Copyright of an intellectual work that is set forth in a permanent form. This study aims to find out how the legal protection of modified motorcycle copyrights in Indonesia, as well as the legal consequences of modified motorcycle copyrights in Indonesia. The research method used is normative legal research by conducting research from library materials or secondary data. Based on the results of the study, Legal Protection of Modified Motorcycle Copyrights in Indonesia is carried out with preventive and repressive measures that protect legal subjects through laws and regulations, including those relating to copyright, which can encourage the acceleration of culture in orderly traffic. The legal consequences of Modified Motorcycle Copyrights in Indonesia that can be applied to overcome traffic violations are carried out by the authorities, so as to create legal stability.